2018
DOI: 10.1097/md.0000000000013068
|View full text |Cite
|
Sign up to set email alerts
|

An evidence-based approach to assess the accuracy of diffusion kurtosis imaging in characterization of gliomas

Abstract: Objective:Accurate and noninvasive pathologic grading of glioma patients before surgery was crucial to guiding clinicians to select appropriate treatment and improve patient prognosis. This study was performed to investigate the potential diagnostic value of diffusion kurtosis imaging (DKI) to distinguish high-grade gliomas (HGGs) from low-grade gliomas (LGGs) based on an evidence-based approach.Methods:Relevant articles that used DKI to distinguish HGG from LGG in Embase, PubMed, China Knowledge Resource Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…To date, there have been only two published meta-analyses which have looked at the diagnostic test accuracy (DTA) of DKI in glioma discrimination and both demonstrated very promising initial results [10,11]. Our systematic review and meta-analysis extend this further by increasing the number of electronic databases, removing language restrictions and broadening the eligibility criteria.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…To date, there have been only two published meta-analyses which have looked at the diagnostic test accuracy (DTA) of DKI in glioma discrimination and both demonstrated very promising initial results [10,11]. Our systematic review and meta-analysis extend this further by increasing the number of electronic databases, removing language restrictions and broadening the eligibility criteria.…”
Section: Discussionmentioning
confidence: 74%
“…Early research is encouraging. Two prior meta-analyses which looked at the diagnostic accuracy of DKI for glioma grading projected a pooled area under the curve (AUC) of 0.94 and 0.96 for MK [10,11]. We attempted to consolidate the preliminary meta-analyses evidence in the topic through an updated systematic review and meta-analysis.…”
Section: Introductionmentioning
confidence: 99%
“…By acquiring data in more than 15 nonlinear directions, both kurtosis metrics (mean, axial, and radial kurtosis) and conventional diffusion metrics (mean, axial, radial diffusivity, and fractional anisotropy) are obtained. Meta-analyses that examined the diagnostic accuracy of DKI for differentiating high- and low-grade gliomas projected a pooled area under the curve of 0.94 and 0.96 for mean kurtosis [ 68 , 69 ]. More recently, Abdalla et al performed an extended and updated meta-analysis and also concluded that DKI has good diagnostic accuracy in differentiating high- from low-grade gliomas [ 70 ].…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%